Metallurgical study of copper objects from the Varanasi region, India (1200 BCE to 400 CE) - Upadhyay P.; Sivarajan R.; Tripathi V.; Upadhyay C. (My University, 2025)
This study aims to investigate ancient Indian copper metallurgy based on selected copper artifacts recovered from India. The collected objects belong to the period c. 1200 BCE to 400 CE. The paper discusses the analysis of seven artifacts from two archaeological sites (Agiabir and Raipura) around the Varanasi region in Northern India. The study explores the manufacturing techniques and alloying practices applied to the artifacts by analyzing the excavated objects using optical microscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray fluorescence spectroscopy. The microstructure of the artifacts revealed the practice of annealing, casting, and forging. Elemental analysis of these objects shows that most of the artifacts are copper–tin alloys, having varying amounts of tin. This study indicates that the tin amount has been varied according to the object's functionality. © 2024 The Author(s). Archaeometry © 2024 University of Oxford.